Konduktivitas Listrik Pulp Kakao dengan Fermentasi dan Pengenceran - Sugito, Heri; Mujasam, Mujasam (BERKALA FISIKA, 2009)
Relation between hydrogen ion exponent (acidity) cacao pulp with energy pass electrics (conductivity) checked to know how ability of cacao pulp at various level of hydrogen ion exponents in sending electrics and also how relation between cacaoes pulps hydrogen ion exponents ably energies pass the electrics.Research done by two treatment that is prose process and fermentation of thinning of cacao pulp. Its way beforehand look for resistivity value (Ï) from cacao pulp. From the resistivity value obtained by conductivity value (Ïƒ) cacao pulp. If connected between cacaoes pulps hydrogen ion exponents with energies pass the electrics out of two the treatment, the result is progressively low degree of acidity of cacao pulp, energy pass the electrics is progressively decline.Relation between hydrogen ion exponent with electrics conductivity at cacao pulp at fermentation process yield equation = 2,84782 + 1,01789 e [-(x-2,5)/0,626)] and at thinning process yield equation Ïƒ = 3,13506 + 0,46513 e [-(x-2,5)/0,20194). On file energy at cacao pulp is known that longer ammeter galvanometer network is attached smaller the electric current so that the energy still be small.